Relative Inequality and Poverty in Germany and the United States Using Alternative Equivalence Scales - Richard V. Burkhauser; Timothy Michael Smeeding; Joachim Merz (Luxembourg Income Study (LIS), 1994)
German and US LIS data are used to compare the relative economic well-being of Germans and Americans in the 1980s. Both official and consumption-based country specific equivalence scales are used.
Keywords: 330